Heavy metals concentration and histopathological profile of some commercial fish species at Makoko Slum Neighbourhood Environment, Lagos, Nigeria - Simeon O. Ayoola (Aceh Journal of Animal Science, 2019)
Potentially harmful substances such as pesticides, heavy metals, and hydro chemicals are often released into the aquatic environment. The objective of the present study was to assess the concentration of lead, copper, cadmium, chromium, and nickel in water samples from two different points (Mid-stream and downstream), also determine the levelsof Lead, Zinc, Manganese and copper in four commercially important fish species, Pseudotolithus senegalensis (croaker fish) and Ethmalosa fimbriata (bonga), Oreochromis mossambicus (Tilapia fish) and Bagrus bayad (silver catfish) from Makoko water body, Yaba, Lagos, Nigeria. Histopathological profile of the fish species selected was also examined. The results were compared to the World Health Organization (WHO) acceptable limit.The concentrations of the heavy metals were analyzed using Perkin Atomic Absorption Spectrophotometer (AAS). Pseudotholithus senegalensishad 3.01±0.02, 2.41±0.02, 3.48±0.01, 1.04±0.10 mg kg-1as the mean concentration of lead, zinc, manganese, and copper respectively, while E. fimbriatahad 1.06±0.02, 2.41±0.02, 4.14±0.01, 1.04±0.10 mg kg-1,O. mossambicushad 2.09±0.02, 3.11±0.04, 2.48±0.02, 0.62±0.01 mg kg-1and B. bayadhad 1.53±0.12, 3.61±0.05, 2.44±0.03, 0.66±0.01 mg kg-1 as the mean concentration of these metals in the tissues of these fishes. The concentrations of heavy metals were higher in the gills compared to other organs. The mean concentration of each heavy metal were varied significantly (p0.05) depending on the species of fish. In the histological analysis of the tissues, there was vacuolation of hepatocytes, inflammation, and necrosis. In the muscle, there was a mild lesion, necrosis, inflammation, and cellular degenerations. But the level of tissue and organ degeneration is more severe in the gills. The study showed that some levels of these metals were within the permissible recommended allowed limit for human consumption. It is concluded that Makoko Lagoon water body and fishes are heavily contaminated with heavy metals.